2016
DOI: 10.15663/tandc.v16i1.108
|View full text |Cite
|
Sign up to set email alerts
|

Applying funds of knowledge theory in a New Zealand high school: New directions for pedagogical practice

Abstract: Teachers and Curriculum is an online peer-reviewed publication supported by Wilf Malcolm Institute of Educational Research (WMIER), Faculty of Education, The University of Waikato, Hamilton, New Zealand. It is directed towards a professional audience and focuses on contemporary issues and research relating to curriculum pedagogy and assessment. ISSN 2382-0349 Notes for ContributorsTeachers and Curriculum welcomes• innovative practice papers with a maximum of 3,500 words, plus an abstract or professional summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Much FoK scholarship has relied on ethnographic research carried out by teachers in visits made to their students’ homes, which González (1995) called “the funds of knowledge methodology” (p. 238), but this approach may accentuate parents’ FoK and will not reveal students’ FoK developed in other contexts (Moll, 2005) 3 . Third, conducting home visits is a very time-consuming process, and some teachers are concerned that they will not be able to implement this for all their students (Esteban-Guitart, Lalueza, Zhang-Yu, & Llopart, 2019; Hogg, 2013). In contrast, in FoI literature pleas are made for a qualitative multimethodological approach to complement the use of in-depth interviews.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much FoK scholarship has relied on ethnographic research carried out by teachers in visits made to their students’ homes, which González (1995) called “the funds of knowledge methodology” (p. 238), but this approach may accentuate parents’ FoK and will not reveal students’ FoK developed in other contexts (Moll, 2005) 3 . Third, conducting home visits is a very time-consuming process, and some teachers are concerned that they will not be able to implement this for all their students (Esteban-Guitart, Lalueza, Zhang-Yu, & Llopart, 2019; Hogg, 2013). In contrast, in FoI literature pleas are made for a qualitative multimethodological approach to complement the use of in-depth interviews.…”
Section: Resultsmentioning
confidence: 99%
“… 3 However, in a number of FoK studies, alternative ways to learn about students’ FoK were used (e.g., Allen et al, 2015; Calabrese Barton & Tan, 2009; Dworin, 2006; Hogg, 2013; Smythe & Toohey, 2009). …”
mentioning
confidence: 99%
“…Dismantling linguistic and cultural barriers experienced by Pacific mothers largely "separated" from the New Zealand culture could encourage them to initiate conversations with teachers on their children's academic progress and be more involved at school. For example, the initial teacher education could equip teachers with the knowledge of Pacific perspectives and values by incorporating them into teacher preparation programmes and materials [55,88]. The concept of assessment can also be broadened to include more holistic measures that are culturally appropriate and cater for the needs of a diverse and multilingual student body [73].…”
Section: Resultsmentioning
confidence: 99%
“…These funds of knowledge were subsequently used in the classroom to relate the curriculum to the students' lives. In the literature several examples can be found that build on this approach (Andrews & Yee, 2006;Ares & Buendía, 2007;Hogg, 2015Hogg, , 2016Lee, 2001;Mercado, 2005;Olmedo, 2004;Rubinstein-Avila, 2006). For instance, Andrews and Yee (2006) collaborated with a teacher to investigate the lives of two minority ethnic children (one Bengali, one Pakistani) in their family and community in the UK.…”
Section: Funds Of Knowledgementioning
confidence: 99%
“…This allowed the teacher to see how these children were engaged in mathematical activities at home, resulting in knowledge that could be drawn on in class. Hogg (2016) discussed how, in cooperation with parents and students, teachers learned about students' FoK and consequently designed learning activities based on these. For example, one teacher scaffolded her students' learning about Roman warriors by encouraging him to use and compare what he already knew about Māori warriors, such as traditional burial practices.…”
Section: Funds Of Knowledgementioning
confidence: 99%